Diabetic impotence: studies of nocturnal erection during REM sleep. Issue 6202 (1st December 1979) - Hosking, D J; Bennet, T; Hampton, J R; Evans, D F; Clark, A J; Robertson, G
Abstract : Nocturnal erections were studied in 30 diabetic patients who complained of impotence and in 11 healthy volunteers. The maximum increase in penile circumference was measured by a penile strain-gauge and recorded on a portable tape-recorder; an external oculogram was recorded simultaneously to identify periods of rapid-eye-movement sleep. The technique gave reproducible results, was acceptable to patients, and was suitable for use in an oridnary hospital ward. Only six diabetics showed a maximum increase in penile circumference of under 15 mm, whereas all but one of the healthy subjects showed maximum increases above this value. Of the six diabetics, five complained of total impotence and had other features of autonomic neuropathy that suggested an organic basis for their impotence. The other patient complained of partial importence, which was probably caused by psychological factors. These findings suggest that the prevalence of organic impotence among diabetics has been overestimated.